FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ABORTUS INKOMPLIT DI RSUD LANTO DG. PASEWANG KABUPATEN JENEPONTO - Bara'padang, Delfiani; Yuliana, Yuliana (STIKES Pasapua Ambon, 2023)
Introduction: The occurrence of incomplete abortion, a miscarriage condition that does not successfully remove all products of conception from the uterus, is a complex event and can have significant health and psychological impacts for women. This study is to determine the factors related to the Incomplete Abortion Event at Lanto Dg. Pasewang Hospital in 2023. Method:. This type of research is a type of research using analytical survey methods using case control study research design. The study sample was divided into case and control samples with a ratio of 1: 1 with the number of respondents as many as 46 people consisting of maternal samples with incomplete abortion as many as 23 people, while the control samples of pregnant women who experienced abortion but not incomplete amounted to 23 people. Results: The results of this study using bivariate test analysis obtained p-value = 0.000, 0.001, 0.003 ≤ α 0.05 means that there is a relationship between age, parity, pregnancy distance, and the incidence of incomplete abortion at Lanto Dg. Pasewang Hospital in 2023, while anemia obtained a p-value of 0.552 > α 0.05 means that there is no relationship between anemia and the incidence of incomplete abortion at Lanto Dg. Pasewang Hospital in 2023. Of the four variables, the age variable was most at risk of incomplete abortion with an OR= 30.790 value. Conclusion: There is a relationship between age, parity, and distance of pregnancy and the incidence of incomplete abortion.